O QUE FAZEM OS HACKERSPACES - Carneiro dos Santos, Otavio; Souza Neto, João; Bernardi da Silva, Ana Paula (LINKSCIENCEPLACE, 2026)
This research analyzes experimental labs known as hackerspaces, community spaces focused on project development and knowledge sharing. Using content analysis and computer-assisted qualitative analysis, this study sought to identify common features among current active hackerspaces. From a starting point of 1.805 listed hackerspaces, hundreds of web pages published by members were classified and reviewed. Then 922 texts were crawled by automatic scripts specially designed for this research, resulting in keywords in English and its equivalents in other languages. The occurrences of these words in texts produced and published in different regions indicate an identity among hackerspaces, noted by the common purpose of events advertising and the promotion of ―making‖ and ―learning‖.